MENGHADIRKAN YESUS KRISTUS YANG MEMBEBASKAN PARA PETANI MISKIN YANG TERSALIB DI PAROKI MARA SATU: Sebuah Sintesa Kristologi Kontekstual - Bobby Steven Timmerman (Jurnal Orientasi Baru, 2014)
The First FABC Plenary Assembly explained that the Asian Church has to participate in a dialogue of life with the poor which involves a genuine experience and understanding of the poverty, deprivation, and oppression of many of the Asian peoples. Among of the Asians poor are the farmers in Mara Satu Parish, Tanjung Selor Diocese of North Kalimantan. This paper presents a christological synthesis based on the context of structural poverty of those poor farmers in dialogue with biblical-christological reflection, mainly the Beatitudes (Matthew 5:3-12). Through his words and acts, Jesus liberated the poor and oppressed in his time. The Church has received from Jesus the mission to help the poor. Therefore, the Church is called to implement its ministry for the poor.